Working with deaf people : a handbook for healthcare professionals - Middleton, Anna. (Cambridge, UK ; New York : Cambridge University Press, 2010)
'Long gone are the days when a deaf person is expected to struggle through a healthcare consultation with a health professional who has inadequate deaf awareness. Legislation now dictates that the onus is on the health professional to utilise the right communication skills. Deafness is very common, meaning that health professionals, whatever their specialist area, can expect to encounter a client with deafness or hearing loss on a daily basis. Working with Deaf People is intended for use as a general reference manual, offering practical advice on how to prepare for the consultation with clients who are deaf or deafblind. Information is offered about language, communication and culture; case studies demonstrate how the messages can be applied in practice. Every health professional, medical and nursing student, whatever their discipline and whatever country they work in, should have a copy of this book'--Provided by publisher.
Includes bibliographical references (p. [173]-186) and index.
Keywords: Communication; Professional-Patient Relations; Hearing Impaired Persons